Thickened carotid intima media thickness and carotid atherosclerosis among lupus nephritis patients: The role of traditional and lupus-specific factors - Sazliyana S.; Mohd Shahrir M.S.; Kong N.C.T.; Tan H.J.; Hamidon B.B.; Azmi M.T. (2024)
Indexed by WOS/ Scopus